Fallow deer (Dama dama dama) management in Roman South-East Britain - Madgwick, Richard; Sykes, Naomi; Miller, Holly; Symmons, Robert; Morris, James; Lamb, Angela L. (Springer, 2013)
This paper presents new carbon, nitrogen and sulphur isotope data for European fallow deer (Dama dama dama) in Roman Britain and discusses results in light of evidence from classical texts, landscape archaeology, zooarchaeology and the limited available samples of metric data. The new isotope data presented here are from Fishbourne Roman Palace (Sussex), two sites on the Isle of Thanet (Kent) and a further two sites in London. In spite of small sample sizes the data make an important contribution to the very limited corpus of scientific research on the species and provide new resolution to the nature of fallow deer movement and management in Roman Britain.